Diversification of Horticultural Processed Products in Roban Village, Singkawang, West Kalimantan: DIVERSIFIKASI PRODUK OLAHAN HORTIKULTURA DI KELURAHAN ROBAN, SINGKAWANG, KALIMANTAN BARAT - Nur Fajar Febtysiana; Nurmala; Th. Candra Wasis; Ichsan; Adi Marjani Pattapa; Revi Sesario; Dody Radiansah; Hillary, Janne; Jaini Fakhruddin (PT. ROCE WISDOM ACEH, 2024)
Singkawang City is a major vegetable producer with significant trade potential. Opportunities for processing vegetables into dried products in Singkawang City are still open and prospective. Vegetable chips can be used as souvenir products for tourists who stop by in Singkawang. The prospect of vegetable chips has not yet been well captured by the farmers of Roban Village. The community service activity (PPM) was done to educate and socialize about diversifying horticultural processed products) to the Roban villagers. This activity was attended by 13 participants who were members of women farmers and Family Empowerment and Welfare (PKK) Movement, using the lecture method followed by demonstrations of spinner usage. In this activity, spinner was also distributed. Monitoring and evaluation of activities is carried out throughout the activity through two-way discussions, pretest and posttest. Referring to the results of the pretest and posttest, the level of public understanding of entrepreneurship, marketing management as well as how to package the chips, indicate improvement.